2019
DOI: 10.1002/bdm.2150
|View full text |Cite
|
Sign up to set email alerts
|

Cheating among children: Temptation, loss framing, and previous cheating

Abstract: Although early economic approaches to misbehavior merely compare the monetary utility of accessible options, self‐concept maintenance models introduce moral considerations to the equation. These assume that people trade off possible gains to be made from moral transgressions with associated decreases in self‐esteem. On the basis of the assumption that the development of moral values among children is weaker than in adults, we expected children's behavior to be close to that of the hypothetical homo economicus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Schindler and Pfattheicher () noted that loss framing increases cheating relative to gain framing. This was also shown by Grolleau et al (), Teschner (), Markiewicz, Malawski, and Tyszka (), and Markiewicz and Gawryluk (). Although this phenomenon is now well established, the important question of which processes produce it remains unanswered.…”
Section: Introductionsupporting
confidence: 77%
“…Schindler and Pfattheicher () noted that loss framing increases cheating relative to gain framing. This was also shown by Grolleau et al (), Teschner (), Markiewicz, Malawski, and Tyszka (), and Markiewicz and Gawryluk (). Although this phenomenon is now well established, the important question of which processes produce it remains unanswered.…”
Section: Introductionsupporting
confidence: 77%
“…Our combined analysis further revealed that gender had no significant effect on over‐reporting. To date, evidence for gender differences in adolescents' cheating behavior is mixed, with some studies finding no effects (Evans & Lee, 2011; Glätzle‐Rützler & Lergetporer, 2015; Maggian & Villeval, 2016) and other studies showing significant gender differences (Cohn & Maréchal, 2018; Markiewicz & Gawryluk, 2019). We found that adolescents whose mothers had a university degree over‐reported fewer points.…”
Section: Discussionmentioning
confidence: 99%
“…This setup gives participants the opportunity to secretly switch to locations with more favorable outcomes. As such switches are unobservable, the task does not require privacy booths (Bucciol & Piovesan, 2011;Fischbacher & Föllmi-Heusi, 2013), deception, or hidden cameras (Evans & Lee, 2010;Heyman et al, 2015;Markiewicz & Gawryluk, 2019;Talwar et al, 2002). Participants played the game repeatedly across 15 rounds and received prizes based on the total number of eyes on the 15 reported dice (one die per round).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some studies have indicated that proposers in the dictator or ultimatum game show a lower dislike for advantageous inequality when outcomes are framed as losses than when outcomes are framed as gains (Lusk and Hudson, 2010;Neumann et al, 2018;Fiedler and Hillenbrand, 2020). Moreover, across die-under-the-cup and coin-toss tasks, people are more motivated to cheat to avoid loss than to make gains of identical size (Van Yperen et al, 2011;Grolleau et al, 2014Grolleau et al, , 2016Schindler and Pfattheicher, 2017;Sun et al, 2017;Markiewicz and Czupryna, 2020;Markiewicz and Gawryluk, 2020). Last, individuals are more likely to approve of obtaining "insider information" in response to hypothetical scenarios (Kern and Chugh, 2009) and more prone to making selfserving mistakes in a die-roll task (Leib et al, 2019) in the loss context than in the gain context.…”
Section: Evidence That Losses (Vs Gains) Decrease Prosocialitymentioning
confidence: 99%